Pelatihan Integrasi Kecerdasan Buatan Digital dalam Pembelajaran Bahasa Inggris di Madrasah - M Labib Al Halim (Al-Qalam Institute, 2023)
This research highlights the importance of digital literacy training and the integration of artificial intelligence in learning to improve teachers' abilities and the quality of English language learning in the digital era. The research evaluates teachers' digital literacy and knowledge of artificial intelligence (AI) and its integration into English language learning. Design quantitative descriptive with survey methods used. Online questionnaires and interviews were applied to English teachers at SMP-MA Diniyah Al-Falahiyah Lamongan to measure digital literacy, knowledge, training experience, and IT and AI media integration in learning. Most teachers have adequate digital skills, but training is still needed to increase digital literacy. Survey results show that most teachers have limited knowledge about AI, with most having never integrated AI into learning.